Malnutrition in Chronic Kidney Disease - Iorember, Franca M. (Frontiers in Pediatrics, 2018)
Patients with chronic kidney disease are at substantial risk of malnutrition, characterized by protein energy wasting and micronutrient deficiency. Studies show a high prevalence rate of malnutrition in both children and adults with chronic kidney disease. Apart from abnormalities in growth hormone-insulin like growth factor axis, malnutrition also plays a role in the development of stunted growth, commonly observed in children with chronic kidney disease. The pathogenic mechanisms of malnutrition in chronic kidney disease are complex and involve an interplay of multiple pathophysiologic alterations including decreased appetite and nutrient intake, hormonal derangements, metabolic imbalances, inflammation, increased catabolism, and dialysis related abnormalities. Malnutrition increases the risk of morbidity, mortality and overall disease burden in these patients. The simple provision of adequate calorie and protein intake does not effectively treat malnutrition in patients with chronic kidney disease owing to the intricate and multifaceted derangements affecting nutritional status in these patients. A clear understanding of the pathophysiologic mechanisms involved in the development of malnutrition in chronic kidney disease is necessary for developing strategies and interventions that are effective, and capable of restoring normal development and mitigating negative clinical outcomes. In this article, a review of the pathophysiologic mechanisms of malnutrition in chronic kidney disease is presented.